Red Guava Juice (Psidium guajava L.) Reduce Oxidative Stress of Toll Gate Collector - Riva Mustika Anugrah; Sugeng Maryanto; Kusmiyati Tjahjono; Martha Irene Kartasurya (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Exposure to air pollution can increase the occurrence of oxidative stress. Research showed that guava can reduce oxidative stress in Sprague Dawley rats. This experiment investigated the effect of red guava juice on oxidative stress in toll collectors. The subjects were 20 toll collectors in the treatment group and 20 in the control group. The treatment group received 250 mL red guava juice for 21 days while the controls did not receive anything. Malondialdehyde (MDA) was measured with thiobarbituric acid (TBA) reaction, food consumption was measured by 3×24 hours’ recall. The data were analyzed by paired t-test, Wilcoxon test, independent t-test, Mann Whitney test, and general linear model. The results showed that the effect of red guava juice on the MDA level was significant in the treatment group (p<0.05). A multivariate analysis showed that the effect of red guava juice to MDA level was significant after controlled by age, carbohydrate intake and initial conditions (p<0.05). Red guava juices of 250 mL for 21 days could reduce malondialdehyde (MDA) levels of toll collectors.